Prevalencia de Babesia bovis en ganado de doble propósito en tres pisos climáticos en el cantón el Chaco - Gaibor Pallo, Gabriel Alejandro (2025)
This study was conducted in the El Chaco canton to analyze various epidemiological factors associated with the prevalence of Babesia spp. in cattle, as well as to evaluate variables such as age, sex, breed, production purpose, degree of tick infestation, and the effectiveness of two diagnostic methods: ELISA and Giemsa. A sample of 90 cattle distributed across different climatic zones was examined, observing a higher concentration of young animals (0–12 months) at altitudes above 2,100 m a.s.l. Females represented 70% of the population, reflecting a productive approach oriented toward dairy and reproductive production. Regarding production purpose, a predominance of the dual-purpose system (43.3%), followed by milk production (34.4%) and beef (22.2%). The Holstein Friesian breed was the most common (60%), followed by Jersey and Girolando. Regarding the degree of infestation, 33.3% of the animals did not present larvae, while another 33.3% showed moderate infestation (5-6 larvae/cm²), indicating a polarized distribution in the cattle population. Regarding the presence of Babesia spp., the ELISA test yielded positive results in 22.2% of animals, while the Giemsa test detected 12.2%, demonstrating differences in sensitivity and specificity between the two methodologies. ELISA demonstrated greater sensitivity (90.91%), while Giemsa presented greater specificity (98.57%). These results are relevant for the diagnosis and control of bovine babesiosis in Andean regions of Ecuador, where the disease was not previously considered endemic.